[(18)F]F-PSMA-1007 Radiolabelling without an On-Site Cyclotron: A Quality Issue - Di Iorio, Valentina (Pharmaceuticals (Basel), 2021)
Radiopharmaceuticals targeting the prostate-specific membrane antigen (PSMA) has become the gold standard for PET imaging of prostate cancer. [(68)Ga]Ga-PSMA-11 has been the forerunner but a [(18)F]F-PSMA ligand has been developed because of the intrinsic advantages of Fluorine-18. Fluorine-18 labelled compounds are usually prepared in centers with an on-site cyclotron. Since our center has not an on-site cyclotron, we decided to verify the feasibility of producing the experimental (18)F(-)labelled radiopharmaceutical [(18)F]F-PSMA-1007 with [(18)F]F(-) from different external suppliers. A quality agreement has been signed with two different suppliers, and a well-established and correctly implemented quality assurance protocol has been followed. The [(18)F]F(-) was produced with cyclotrons, on Nb target, but with different beam energy and current. Extensive validation of the [(18)F]F-PSMA-1007 synthesis process has been performed. The aim of this paper was the description of all the quality documentation which allowed the submission and approval of the Investigational Medicinal Product Dossier (IMPD) to the Competent Authority, addressing the quality problems due to different external suppliers. The result indicates that no significant differences have been found between the [(18)F]F(-) from the two suppliers in terms of radionuclidic and radiochemical purity and [(18)F]F(-) impacted neither the radiochemical yield of the labelling reaction nor the quality control parameters of the IMP [(18)F]F-PSMA-1007. These results prove how a correct quality assurance system can overcome some Regulatory Authorities issue that may represent an obstacle to the clinical use of F-18-labelled radiopharmaceuticals without an on-site cyclotron.